Elaboration Of Nahdlatul Ulama Jember Views On The Reasons For The Use Of Ḥadīth Ḍa‘Īf - Kasman, Kasman; Hariyanto, Al Furqon Dono (Fenomena, 2023)
Among scholars, there are differences of view regarding the use of ḥadīth ḍa‘īf. This difference in views has little effect on the religious views of Islamic organizations in Indonesia, including the Nahdlatul Ulama (NU). This paper aims to elaborate the view of the Nahdlatul Ulama Jember against the ḥadīth ḍa'īf, either related to law halal and haram, or about faḍā'il al-a'māl, targhīb, and tarhīb. By using the descriptive qualitative method, it was found that: (a) theoretically, NU Jember follows the views of jumhūr ‘ulamā’ who reject the use of ḥadīth ḍa'īf in the field of the law of halal and haram, but practically still tolerate ḥadīth ḍa'īf particular in the area of the law of halal and haram; (c) in the field of faḍā'il al-a'māl, targhīb, and tarhīb, Nahdlatul Ulama Jember allow argues with the ḥadīth ḍa'īf. What is meant by faḍā’il al-a‘māl in the view of the Nahdlatul Ulama Jember is deeds that are not obligatory (Fardhu), namely Sunnah worship, an expected worship reward by doing it.